2014
DOI: 10.1016/j.applanim.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic selection for residual feed intake on behavioral reactivity of castrated male pigs to novel stimuli tests

Abstract: Increasing feed efficiency in swine is important for increasing sustainable food production and profitability for producers; therefore, this is often selected for at breeding. Residual feed intake (RFI) can be used for the genetic selection of pigs for feed efficiency. In our selection project, low-RFI pigs consume less feed for equal weight gain compared to their less efficient, high-RFI counterparts. However, little is known about how feed efficiency influences the pig's behavioral reactivity toward fear-eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“… Meunier-Salaün et al (2014) showed that a reduced physical activity in pigs from a line selected for low RFI contributed significantly to their improved feed efficiency. Sadler et al (2014) observed that gilts from a line selected for low RFI spent less time standing, more time sitting, and were less active overall than pigs from a control line, and Colpoys et al (2014) showed that low RFI male pigs were less active than those from a high RFI line. In growing cattle, variation in physical activity was estimated to account for approximately 10% of the variation in RFI ( Herd et al, 2004 ).…”
Section: Selection For Feed Efficiency In Livestock: Further Domesticmentioning
confidence: 99%
See 1 more Smart Citation
“… Meunier-Salaün et al (2014) showed that a reduced physical activity in pigs from a line selected for low RFI contributed significantly to their improved feed efficiency. Sadler et al (2014) observed that gilts from a line selected for low RFI spent less time standing, more time sitting, and were less active overall than pigs from a control line, and Colpoys et al (2014) showed that low RFI male pigs were less active than those from a high RFI line. In growing cattle, variation in physical activity was estimated to account for approximately 10% of the variation in RFI ( Herd et al, 2004 ).…”
Section: Selection For Feed Efficiency In Livestock: Further Domesticmentioning
confidence: 99%
“…Efficient chickens have been reported to show a lower sensitivity to environmental disturbances than inefficient chickens ( Morrison and Leeson, 1978 ; Katle et al, 1984 ). In pig, Colpoys et al (2014) showed that male pigs from a line selected for low RFI displayed a shorter duration of freezing, froze less frequently, and attempted to escape less frequently than high-RFI pigs ( Colpoys et al, 2014 ). In the same pig lines, Sadler et al (2014) showed that gilts from the low-RFI line tended to have lower baseline cortisol concentrations and were less responsive to an ACTH challenge than gilts from the high-RFI line ( Jenkins et al, 2013 ).…”
Section: Selection For Feed Efficiency In Livestock: Further Domesticmentioning
confidence: 99%
“…In swine, feed efficient pigs from lines divergently selected for RFI demonstrated fewer arousal and fear behaviors and longer time to approach novel stimuli (Colpoys et al, 2014).…”
Section: Correlated Response To Selectionmentioning
confidence: 99%
“…In G8 and G9, pigs from the Low and High RFI lines were subjected to two tests (human approach and novel object tests) to measure behavioral reactivity to novel, feareliciting stimuli (Colpoys et al, 2014;Colpoys et al, 2015). In G8 and for both tests, barrows from the Low RFI line were observed to have fewer head movements (P ≤ 0.02), defecate less frequently (P ≤ 0.03), freeze in place for shorter amounts of time (P = 0.05), freeze less frequently (P < 0.0001), cross fewer zones (test area was split into 4 zones based on distance from novel object, P < 0.0001), and took longer (48 to 52 seconds) to approach the novel object (P ≤ 0.04) compared to High RFI barrows (Colpoys et al, 2014). During the human approach test, Low RFI barrows also tried to escape the area fewer times than High RFI barrows (P = 0.001).…”
Section: Grow-finishmentioning
confidence: 99%
“…Selection for lower RFI has also been reported to have limited negative impacts on meat quality , response to fear-eliciting stimuli and welfare (Colpoys et al, 2014;Colpoys et al, 2015), reproduction , and immune response (Mpetile et al, 2015), including response to porcine reproductive and respiratory virus (Dunkelberger et al, 2015). Additionally, various metabolic mechanisms have been found to contribute to the increased efficiency of the Low RFI line within the ISU selection project, including decreased degradation of protein , less reactive oxygen species production by mitochondrion in muscle and liver tissues , and increased energy and nutrient digestibility .…”
Section: Introductionmentioning
confidence: 99%